(untitled) (Oil and Gas Engineering, 2017)
Offered construction of layer tester, which allows to conduct the selective collectors test in the multicyclic mode at the different depressions sizes and provides possibility of closing-opening of his valves the axial boring column moving. Keywords: tester of layers, selective tests, cracks type collectors, depression on a layer.